A Pragmatic Analysis of Deixis in Selected Songs from The Album Being Funny in a Foreign Language for ELT - Putri, Atik Okta Setya; Budiman, Theresia Cicik Sophia; Setyorini, Ajeng (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Meaning extends beyond the literal form of language since it is a dynamic system. Defixis is a remarkable pragmatic phenomenon in language usage; it refers to a collection of statements whose meaning is contingent upon characteristics including speaker, place, time, discourse, and social context. Everyday speech, literary works, and creative expressions (such as song lyrics) all include deixis. Songs are great resources for linguistic analysis and language acquisition because they provide rich contextual references, which are a result of the language's genuine usage. There is a dearth of literature on pragmatics in literary and media texts, although there is some study on deixis in song lyrics, especially as it pertains to ELT. The purpose of this research is to dissect the album Being Funny in a Foreign Language for its deixis and the pragmatic roles they play in certain tracks. Based on Levinson's (1983) theory, this research used a qualitative content analysis methodological approach to classify deixis as follows: personal, temporal, geographical, discourse, and social. Five songs were chosen at random using a purposive sample strategy to gather data for the investigation. As a source of information, documentation procedures were used to gather the official lyrics of the five songs. In addition, the data were evaluated by classifying different kinds of deixis and then determining how often each kind occurred. Out of a total of 482 deixis expressions, 455 were found to be personal (94.40%), 2 to be spatial (0.41%), 7 to be temporal (1.45%), 17 to be discourse (3.53%), and 1 to be social (0.21%), according to the findings. The study revealed that personal deixis was the most common form of deixis, with discourse, time, location, and social deixis following closely behind. Each of these types added to the rich contextual meaning found in the song lyrics. This discovery suggests that students' comprehension of pragmatic studies, particularly as it pertains to deixis, might be enhanced by using song lyrics as realistic teaching resources.